SIK2 activates the autophagy‒apoptosis pathway through SP1 regulation to inhibit the progression of hepatocellular carcinoma - Fan, Sheng; Zhang, Yan; Ma, Pengcheng; Hou, Huanan; Niu, Ruiqi; Wang, Ziming; Zhang, Jinguo; Xia, Yunhong; Pan, Yueyin (Frontiers in Pharmacology, 2025)
Hepatocellular carcinoma (HCC) ranks as the sixth most prevalent cancer globally and is the fourth leading cause of cancer-related mortality, characterized by limited treatment options and an unfavorable prognosis. Salt-inducible kinase 2 (SIK2), a member of the AMP-activated protein kinase (AMPK) family, regulates cellular processes, including metabolism, autophagy, and apoptosis. However, its specific role in HCC remains unclear. This study assessed the clinical relevance and biological function of SIK2 in HCC via bioinformatics, immunohistochemistry (IHC), cell assays, signaling pathway analyses, and animal models. The results demonstrated that high SIK2 expression was associated with improved patient survival, modulation of the immune microenvironment, and suppression of tumor progression. Mechanistically, SIK2 inhibited HCC cell proliferation, migration, and invasion and promoted autophagy through increased autophagic flux. However, due to impaired autophagic flux, apoptosis is induced. This study highlights the significant clinical relevance of SIK2 in primary liver cancer and its multifaceted roles in tumor biology. SIK2 serves as an independent protective prognostic factor and may exert a tumor-suppressive effect by modulating the tumor microenvironment, autophagy, and apoptosis. Elevated SIK2 expression was strongly linked to better prognosis in HCC patients, highlighting its promise as both a prognostic indicator and a potential therapeutic target. Future research should focus on clarifying the precise molecular mechanisms involving SIK2 and investigating its potential for clinical therapeutic applications.